Late myocarditis: Clinical aspects and diagnostic implications (Research, Society and Development, 2025)
event, vaccination, or exposure to certain pharmacological agents. Its diagnosis represents a clinical challenge due to the variability of symptoms and its similarity to other heart diseases, requiring precise and multidisciplinary diagnostic approaches. The general objective of this study is to analyze the relationship between late myocarditis and drug use, considering clinical, diagnostic aspects and implications for pharmaceutical practice. The methodology adopted was an integrative literature review, with a search for scientific articles published between 2020 and 2025 in the Google Scholar, PubMed, and SciELO databases. Studies that addressed clinical cases, systematic reviews, and reports correlating late myocarditis with drug use, especially antivirals, immunomodulators, and vaccines, were selected.After reading and critically analyzing the texts, the data were organized and compared according to the frequency of drug associations and the reported clinical presentation. The results showed that certain medications can trigger delayed cardiac inflammatory responses, especially in individuals with a genetic predisposition or a history of recent viral infections. Cases associated with the use of immunotherapeutics and vaccines were described, highlighting the need for pharmacological surveillance. It is concluded that the pharmacist's role is essential in the early identification of adverse reactions and in the pharmacotherapeutic monitoring of patients using medications potentially associated with delayed myocarditis. Further studies are recommended to deepen the understanding of pathophysiological mechanisms and to improve prevention and diagnostic strategies.